Retrospective study of risk factors for urethral stricture after transurethral resection of prostate among the elderly in Chengdu, China - Xiaoping, Duan (2025)
Benign prostatic hyperplasia (BPH) is becoming increasingly prevalent, and although transurethral resection of the prostate (TURP) remains the standard surgical treatment, late postoperative urethral stricture remains a potential complication. This cross-sectional study aimed to identify risk factors for urethral stricture following TURP. Clinical data from 400 BPH patients (mean age, 74.31 ± 6.70 years) who underwent TURP at Chengdu University Affiliated Hospital between June 2020 and June 2023 were retrospectively analyzed. This study divided the data into two groups: the urethral stricture group and the non-urethral stricture group. All data were analyzed using univariate and multivariate logistic regression analysis (P < 0.05 was set as the significance criterion). A total of 35 patients (8.75%) developed urethral stricture. Multivariate analysis identified age (OR = 1.121, 95% CI: 1.044–1.204, P = 0.002), prostate size (OR = 1.038, 95% CI: 1.014–1.062, P = 0.002), preoperative indwelling catheter (OR = 5.413, 95% CI: 1.872 – 15.655, P = 0.002), and postoperative indwelling catheter time (OR = 2.147, 95% CI: 1.405–3.280, P < 0.001) as independent risk factors for urethral stricture, whereas preoperative urethral dilation (OR = 0.049, 95% CI: 0.011–0.220, P < 0.001) was an independent protective factor. The nomogram prediction model established based on the above independent influencing factors (AUC = 0.916) has good application prospects in clinical diagnosis and risk assessment